Interleukin 9 serum level and single nucleotide polymorphism in patients with asthma - Mahdaviani, Seyed Alireza; Eskian, Mahsa; Khorasanizadeh, Mirhojjat; Bashardoost, Bahram; Tashayoie Nejad, Sabereh; Jamaati, Hamid Reza; Rezaei , Arezou; Sadr , Maryam; Aryan , Zahra; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2021)
Background:  Asthma is a chronic inflammatory disease of airways which accounts for a huge economic, morbidity and mortality burden. There are different cytokines that contribute to asthma pathophysiology. Learning about these cytokines leads to attaining novel anti-inflammatory treatments for asthma control.Objectives: The objective of this study is to investigate the association between interleukin-9 serum level and gene polymorphism with asthma susceptibility.Methods: This was a case-control study of 70 asthmatic patients and 77 healthy control adults aged 18-60. Asthma diagnosis and severity were based on physician diagnosis, pulmonary function test (PFT) and 2016 guild line of Global Initiative for Asthma (GINA). Interleukin 9(IL -9) serum level was measured using sandwich enzyme linked immunosorbent assay.  IL9 promoter single nucleotide polymorphism (SNP) (rs2069882) was also assessed using Real-Time PCR System.Results: There was no significant association between IL-9 SNP polymorphism and asthma. IL-9 serum level was significantly associated with asthma susceptibility (p value= 0.016) and absolute eosinophil count (AEC) (P value=0.033) however its corelation with atopic asthma type, asthma sivierity and Immunoglubin E serum level were not statistically significant.Conclusion: Although there was no association between IL-9 SNP and asthma, but IL-9 serum level was significantly correlated with asthma susceptibility and AEC.